The clinical and neurocognitive functional changes with awake brain mapping for gliomas invading eloquent areas: Institutional experience and the utility of The Montreal Cognitive Assessment - Wang, Yuan; Guo, Shaochun; Wang, Na; Liu, Jinghui; Chen, Fan; Zhai, Yulong; Wang, Yue; Jiao, Yang; Zhao, Wenjian; Fan, Chao; Xue, Yanrong; Gao, GuoDong; et al. (Frontiers in Oncology, 2023)
Objective: Awake craniotomy with intraoperative brain functional mapping effectively reduces the potential risk of neurological deficits in patients with glioma invading the eloquent areas. However, glioma patients frequently present with impaired neurocognitive function. The present study aimed to investigate the neurocognitive and functional outcomes of glioma patients after awake brain mapping and assess the experience of a tertiary neurosurgical center in China over eight years. Methods: This retrospective study included 80 patients who underwent awake brain mapping for gliomas invading the eloquent cortex between January 2013 and December 2021. Clinical and surgical factors, such as the extent of resection (EOR), perioperative Karnofsky Performance Score (KPS), progression-free survival (PFS), and overall survival (OS), were evaluated. We also used the Montreal Cognitive Assessment (MoCA) to assess the neurocognitive status changes. Results: The most frequently observed location of glioma was the frontal lobe (33/80, 41.25%), whereas the tumor primarily invaded the language-related cortex (36/80, 45%). Most patients had supratotal resection (11/80, 13.75%) and total resection (45/80, 56.25%). The median PFS was 43.2 months, and the median OS was 48.9 months in our cohort. The transient (less than seven days) neurological deficit rate was 17.5%, whereas the rate of persistent deficit (lasting for three months) was 15%. At three months of follow-up, most patients (72/80, 90%) had KPS scores > 80. Meanwhile, compared to the preoperative baseline tests, the changes in MoCA scores presented significant improvements at discharge and three months follow-up tests. Conclusion: Awake brain mapping is a feasible and safe method for treating glioma invading the eloquent cortex, with the benefit of minimizing neurological deficits, increasing EOR, and extending survival time. The results of MoCA test indicated that brain mapping plays a critical role in preserving neurocognitive function during tumor resection.